Hepatitis C virus 5′ untranslated region variability correlates with treatment outcome. Issue 8 (13th October 2013) - Bukowska‐Ośko, I.; Radkowski, M.; Pawełczyk, A.; Rosinska, M.; Caraballo Cortés, K.; Płoski, R.; Berak, H.; Horban, A.; Stanczak, J.; Fic, M.; Laskus, T.
Summary Hepatitis C virus (HCV) variability affects viral–host interactions. We analysed HCV 5′untranslated region (5′UTR) in sera and peripheral blood mononuclear cells (PBMC) from chronic hepatitis C patients undergoing antiviral treatment. We studied 139 patients treated with pegylated interferon and ribavirin. The primary endpoint was a sustained virological response (SVR) defined as negative HCV RNA level 24 weeks after the end of therapy. 5′UTR was analysed by single‐strand conformational polymorphism (SSCP) and sequencing. The pretreatment SSCP pattern in serum and PBMC differed in 26 (18.7%) patients. During therapy, the SSCP pattern remained stable in 65 (60.8%) patients, number of bands declined in 16 (15.0%), and in 18 (16.8%) patients, changes were qualified as 'shift' indicating change in band positions. In univariate analysis, there was a significant (P ≤ 0.05) positive association between SVR and pretreatment serum and PBMC dissimilarities, initial viral load <106 IU/mL, IL‐28B CC genotype of the rs12979860 single nucleotide polymorphism and change in the SSCP band pattern (either 'shift' or decline) In multivariable analysis, only low initial viral load, IL‐28B genotype, and changes in the SSCP band pattern were independent factors associated with SVR. In conclusion, stability of 5′UTR correlated with infection persistence, while changes correlated with SVR.